Subrecentni premiki na Orlah - Placer, Ladislav (Geologija, 2004)
At the eastern margin of the Ljubljansko barje (Ljubljana moor) smaller faultscan be seen along which part or the whole colluvial cover is displaced. The age of the colluvium is not determined therefore at the moment fault are treated as subrecent. Similar the same phenomenon was seen at the Postojna area.
Keywords: Dinaridi; geološke raziskave; Ljubljana Marshes; Ljubljansko barje; prelomi; premiki; tektonika